Asymmetric Synthesis of Cyclopentane‐Substituted Oxindoles via Organocatalytic Desymmetrization of Cyclopent‐4‐ene‐1, 3‐diones. Issue 11 (8th May 2017) - Zhi, Ying; Zhao, Kun; Wang, Ai; Englert, Ullrich; Raabe, Gerhard; Enders, Dieter
Abstract: The highly enantioselective desymmetrization of prochiral cyclopent‐4‐ene‐1, 3‐diones has been developed via an organocatalytic Michael reaction. This desymmetrization protocol is efficiently catalyzed by 10 mol% of a bifunctional squaramide, offering a short entry into a series of cyclopentane‐substituted oxindoles bearing two quaternary and one tertiary stereocenters in good yields and high stereoselectivities. Abstract :